Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective - Kata Zsófia Prém, Laura Kovács-Berényi; Benyusz , Márta; Zombory, Katarzyna (2025)
The volume Child-Friendly Justice: The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective explores how children’s procedural rights, in particular their right to be heard and to participate, are implemented in judicial and administrative proceedings across Central Europe. Bringing together contributions from leading experts in the region, it examines international and European standards on child-friendly justice and analyses how these norms are reflected in national legislation, court practice, and institutional safeguards. By combining comparative legal analysis with practical insights, the book offers an up-to-date overview of the achievements, challenges, and emerging good practices in ensuring that justice systems are genuinely responsive to the needs and rights of children.This volume offers a timely and insightful contribution to the evolving discourse on child-friendly justice, highlighting Central Europe’s specific legal developments, practical experiences, and future directions in strengthening children’s participation rights.